Aktivitas Pinjol dan Bahaya Riba Terselubung di dalamnya - Qonita; Melja Safitri; Dina Marni (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2024)
The phenomenon of online loans (pinjol) presents a quick financial solution but carries risks, particularly regarding the practice of riba, which is prohibited in Islam. This research analyzes the activity of online loans from an Islamic perspective, covering the legal aspects of loans in Sharia law, as well as the social, economic, and psychological impacts. Islam permits loans based on qiradh, which emphasize justice and mutual help without riba. However, online loans often contain elements of riba, either in the form of fixed interest or late payment penalties, which can harm users. This study also discusses the negative impacts of riba, such as inflation, economic injustice, and financial crises. The proposed solutions include the implementation of zakat, infaq, and sadaqah concepts, as well as financial literacy education to avoid the traps of online loans. By understanding the legal and adverse effects of riba, this research aims to raise awareness and provide guidance for the community to lead a more blessed financial life in accordance with Islamic principles.